Climate influences on female survival in a declining population of southern elephant seals (Mirounga leonina). Issue 16 (27th July 2021) - Volzke, Sophia; McMahon, Clive R.; Hindell, Mark A.; Burton, Harry R.; Wotherspoon, Simon J.
Abstract: The Southern Ocean has been disproportionately affected by climate change and is therefore an ideal place to study the influence of changing environmental conditions on ecosystems. Changes in the demography of predator populations are indicators of broader shifts in food web structure, but long‐term data are required to study these effects. Southern elephant seals ( Mirounga leonina ) from Macquarie Island have consistently decreased in population size while all other major populations across the Southern Ocean have recently stabilized or are increasing. Two long‐term mark‐recapture studies (1956–1967 and 1993–2009) have monitored this population, which provides an opportunity to investigate demographic performance over a range of climatic conditions. Using a 9‐state matrix population model, we estimated climate influences on female survival by incorporating two major climatic indices into our model: The Southern Annular Mode (SAM) and the Southern Oscillation Index (SOI). Our best model included a 1 year lagged effect of SAM and an unlagged SOI as covariates. A positive relationship with SAM1 (lagged) related the previous year's SAM with juvenile survival, potentially due to changes in local prey availability surrounding Macquarie Island. The unlagged SOI had a negative effect on both juvenile and adult seals, indicating that sea ice dynamics and access to foraging grounds on the East Antarctic continental shelf could explain the different contributions of ENSO events on the survival of females in this population. Abstract : This research investigated the influence of large‐scale climate modes (SAM and SOI) on female southern elephant seal survival (φ) by creating demographic models from historic capture‐mark‐recapture data. Map of the Southern Ocean from Tasmania (top) to East Antarctica and the Ross Sea (bottom) with Macquarie Island location marked by a small circle. Surrounding Antarctica, the Polar Front (blue line), 60th parallel south, (gray circle) and winter sea ice extent (white) are overlaid. Top right: Vegetation map of Macquarie Island (adapted from the Australian Antarctic Data Centre map no. 13106) and stylized illustration of a female southern elephant seal, Mirounga leonina (artwork by: Sophia Volzke).